2012
DOI: 10.1079/pavsnnr20127010
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of organic agriculture in temperate regions.

Abstract: Can organic agriculture elaborate a scientifically based, resource-efficient and agroecological approach to low-input farm management? This review examines the literature from temperate regions, with a particular emphasis on Canadian and US studies that relate to environmental and ecological impacts of organic agriculture with respect to (i) soil organic matter storage, (ii) soil quality/soil health, (iii) nutrient loading and risks of off-farm nutrient and agrochemical losses, (iv) biodiversity and (v) energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 131 publications
0
18
0
Order By: Relevance
“…Syntheses of published research suggest soil responses to organic production practices are positive with respect to improving soil function through the enhancement of biophysical properties and processes [111,112]. Such soil biophysical improvements are attributed to the emphasis of organic farming on diverse crop rotations, including perennial forages, as well as application of carbon-rich soil amendments [113].…”
Section: Organic Conservation Tillage Effects On Soil Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses of published research suggest soil responses to organic production practices are positive with respect to improving soil function through the enhancement of biophysical properties and processes [111,112]. Such soil biophysical improvements are attributed to the emphasis of organic farming on diverse crop rotations, including perennial forages, as well as application of carbon-rich soil amendments [113].…”
Section: Organic Conservation Tillage Effects On Soil Qualitymentioning
confidence: 99%
“…It is important to acknowledge reviewed studies focused on near-surface soil responses to applied treatments, and while certainly justified from the standpoint of inferring treatment effects on soil erosion, water infiltration, and nutrient conservation [150], the lack of characterization of subsoil conditions and an absence of soil bulk density data compromises our capacity to accurately resolve treatment effects on soil nutrient stocks [112,151]. Supplementing whole-profile assessments with soil bulk density measurements in future evaluations will strengthen conclusions regarding organic conservation tillage system effects on soil quality.…”
Section: Synthesis and Recommendationsmentioning
confidence: 99%
“…Reviews and meta-analyses revealed that the OFS has greater soil carbon content and less soil erosion compared with conventional systems [4][5][6]. Different works also reported that the agrosystem biodiversity is improved in the OFS [5,7,8]. In addition, synthetic pesticides and fertilizers are not allowed, and there is a reduction of nitrate leaching and greenhouse gas emissions in comparison with the conventional farming system [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Different works also reported that the agrosystem biodiversity is improved in the OFS [5,7,8]. In addition, synthetic pesticides and fertilizers are not allowed, and there is a reduction of nitrate leaching and greenhouse gas emissions in comparison with the conventional farming system [3,8,9]. However, since the OFS has lower land-use efficiency than the conventional system, these positive effects are less pronounced and in sometime reversed when expressed per unit product [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In arable systems, it includes organic management and conservation tillage practices (Hobbs et al, 2008). These improved variations of 2 tillage (no till, chisel, disk, sweep till types of reduced tillage ), alone or combined, have shown to be effective in adapting to environmental demands (Lal, 2009) by, for example reducing soil erosion (Lynch, 2012).…”
Section: Introductionmentioning
confidence: 99%